Modern Tajik Constitutionalism: formation specificity and evolution - G I Muromtsev; Sh K Khakimov (RUDN Journal of Law, 2012)
The article analyses the morden period of the constitutionalism development in Tajik respublic as a post-Soviet state using historical and legal method